Chocs/contre choc pétroliers et investisssements étrangers au Nigéria - Quiers-Valette, Suzanne (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1990)
The problems linked to oil profits have been the subject of numerous studies. Few of these studies, however, have dealt with the specific problem of the impact of oil price shocks and return shocks on foreign investments in revenue-generating countries. This paper seeks to analyze the case of Nigeria which has been and still is a key country for the international oligopolies, thanks to the sheer size of its market and its oil wealth. In the face of Africa 's current decline Nigeria is, with South Africa, a potential keystone state that could in time bind together other states into a regional bloc with good prospects for growth. This possible unifying role, however, seems to depend on foreign investment picking up. It is therefore essential to understand better the extent to which foreign investment was spurred from 1973 onwards by the oil boom and what the consequences were of the crisis that began in 1982.